2020
DOI: 10.1073/pnas.1916820117
|View full text |Cite
|
Sign up to set email alerts
|

A cell atlas of the adultDrosophilamidgut

Abstract: Studies of the adult Drosophila midgut have led to many insights in our understanding of cell-type diversity, stem cell regeneration, tissue homeostasis, and cell fate decision. Advances in single-cell RNA sequencing provide opportunities to identify new cell types and molecular features. We used single-cell RNA sequencing to characterize the transcriptome of midgut epithelial cells and identified 22 distinct clusters representing intestinal stem cells, enteroblasts, enteroendocrine cells (EEs), and enterocyte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
158
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(225 citation statements)
references
References 82 publications
21
158
0
Order By: Relevance
“…2F), while C3 was particularly enriched in receptors for neurotransmitters and neuropeptides/hormones like acetylcholine ( acm2 and acha6 ), GABA ( plcl2 ), FMRF-amide ( fmar ), gonadotropin ( gnrr2 ) and somatostatin ( ssr5 ). Even though the C3 cluster contained cells that expressed neurotransmitter and neurohormone receptors, we think this cluster could largely contain gut and muscle cells based on expression of these types of receptors in these cell types in other taxa (Florey and Rathmayer, 1978; Walker et al, 1993; Terra et al, 2006; Crisp et al, 2010; Mirabeau and Joly, 2013; Hung et al, 2020; Wu et al, 2020a). Receptors for acetylcholine, FMRF-amide and GABA have been reported to be localized to the body wall muscle in earthworms and leeches (Walker et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2F), while C3 was particularly enriched in receptors for neurotransmitters and neuropeptides/hormones like acetylcholine ( acm2 and acha6 ), GABA ( plcl2 ), FMRF-amide ( fmar ), gonadotropin ( gnrr2 ) and somatostatin ( ssr5 ). Even though the C3 cluster contained cells that expressed neurotransmitter and neurohormone receptors, we think this cluster could largely contain gut and muscle cells based on expression of these types of receptors in these cell types in other taxa (Florey and Rathmayer, 1978; Walker et al, 1993; Terra et al, 2006; Crisp et al, 2010; Mirabeau and Joly, 2013; Hung et al, 2020; Wu et al, 2020a). Receptors for acetylcholine, FMRF-amide and GABA have been reported to be localized to the body wall muscle in earthworms and leeches (Walker et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In C. teleta , FMRF-amide + neurons have been shown to be associated with the midgut (Meyer et al, 2015). Both glutamate and GABA signaling have been reported in midgut epithelial cells in insects (Terra et al, 2006; Hung et al, 2020). Somatostatin/allatostatin-C encodes for a neuropeptide family of hormones that are expressed in D. melanogaster midgut endocrine cells (Wu et al, 2020a), while octopamine GPCRs have been reported in the annelid P. dumerilii and the priapulid Priapulus caudatus where they were shown to be activated in presence of dopamine, tyramine and octopamine ligands (Bauknecht and Jekely, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The protein maturation of the prohormones into multiple bioactive peptides in EEs is processed by a conserved prohormone convertase Amon and, probably, other putative enzyme homologs, like dCPD, Phm, and Pal1/2 (Reiher et al, 2011). Emerging single-cell RNAseq (scRNAseq) technologies have identified additional gut-peptide hormones in the EEs (Guo et al, 2019;Hung et al, 2020; Table 1). Even though several gut-peptide hormones such as DH31 and Tk were previously shown by in vitro assays to stimulate gut mobility and possible nutrient delivery decades ago (Siviter et al, 2000;LaJeunesse et al, 2010), the investigation of their physiological roles is largely hampered due to lack of genetic tools.…”
Section: Ee-derived-peptide Hormonesmentioning
confidence: 99%
“…Single-cell RNAseq and biochemical analysis indicate that Tk + EEs also produce DH31, Burs, NPF, Gpb5, and Nplp2, in different regions of the midgut (Chen et al, 2016a;Guo et al, 2019;Hung et al, 2020). Another study using the Tk-g-Gal4 revealed that gut NPF non-autonomously controls matinginduced proliferation of germline stem cells via ovarian NPF receptor (NPFR; Ameku et al, 2018).…”
Section: A B Cmentioning
confidence: 99%
“…In particular, scRNA-seq technology is widely used to characterize the responses of various cell types to severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection (Chua et al, 2020, Zhu et al, 2020, Wilk et al, 2020). In Drosophila , one of the major model organisms, the cell lineage characteristics in many tissues have been identified using scRNA-seq, such as the midgut (Hung et al, 2020), blood cells or hemocytes (Tattikota et al, 2020, Cattenoz et al, 2020), ovary (Jevitt et al, 2020, Slaidina et al, 2020), and brain (Davie et al, 2018). However, the application of scRNA-seq technology to determine cell subsets and cell lineages is rare in other insects.…”
Section: Introductionmentioning
confidence: 99%